Hubungan Orang Tua dan Anak Dari Sudut Padang Ilmu Psikologi - Brahmana, Karina Meriem Beru (LPPM Universitas HKBP Nommensen, 2026)
This community service activity was conducted through a seminar entitled “Parent-Child Relationships from a Psychological Perspective”, aimed at enhancing the quality of relationships between parents and their children. The seminar took place at GBKP Runggun Sikeben Congregation, Tanah Karo, and was attended by parents along with their adolescent and adult children. Communication problems, perception gaps, and a lack of understanding of children’s personalities and developmental stages often trigger conflicts within families. This seminar offered a psychological approach to building healthy relationships, emphasizing the importance of two-way communication, empathy, and an understanding of personal characteristics and human developmental stages—from early childhood to adulthood. The seminar was delivered in an interactive and reflective manner. The outcomes showed that participants gained new insights into the role of parents as companions to their children and recognized the need to establish open and empathetic communication within the family. This activity positively contributed to increasing psychological awareness in parenting practices and opened opportunities for further collaboration in fostering harmonious family relationships.